Implementasi Literasi Media yang Diberikan Orangtua terhadap Pembentukan Karakter Anak di Desa Sumbul, Kecamatan Kabanjahe Kabupaten Karo - Sinaga, Husnia Amro Br; Hafizah, Fadilla (YASIN, 2023)
Media literacy is usually consumed by adults parents, because the term media literacy is obtained in the student environment, but over time media literacy has also reached the community. With the rapid development in broadcasting and publishing, it is now able to bring changes to the joints of life. Media literacy is one form of community effort in maintaining positive values as wise media users. With the development and progress of the times that have given rise to technology, it now gives a very big change and is able to lead all divisions in the lives of Indonesian people. Considered in children and adolescents who are elements for Indonesian society. Considered in children and adolescents who are elements for Indonesian society. One of the state assets that ensures the continuity of leadership is adolescents, so what is used as an agent of change is a gradual study of media literacy, and is expected to ensure critical adolescents in becoming media users. In combating mass media exposure, media literacy activities carried out by the community make protection for audiences from attacks broadcast by mass media. media activities in Indonesia are more feared for fear of causing negative impacts on a group of people who are easily affected by negative content. Parents who care about their children will not provide physical health alone, but maintain mental health as well. And because his awareness of his child's education is very large, parents there are aware that his role as the person in charge for the implementation of media literacy is himself because the child's character is fully formed from an early age from what he hears and what he sees. If it is good that he sees and hears, then it is good for the character that is formed.